Idea Art : A Critical Anthology - Battcock, Gregory; Ashton, Dore; Benthall, Jonathan; Bernstein, Cheryl; Burnham, Jack; Kosuth, Joseph; Lippard, Lucy; Meyer, Ursula; Perreault, John; Rose, Arthur; Rosenberg, Harold (New York : E.P. Dutton & Co, 1973)
Heizer, Michael ; Nitsch, Hermann ; Weiner, Lawrence ; Buren, Daniel ; Bochner, Mel ; LeWitt, Sol ; etc.
Engels
boek